Description ofa Blockcourse in Medical Informatics - Hasnian, A. (Methods of Information in Medicine, 1989)
This paper describes a blockcourse in medical informatics. The course is presented to fourth, fifth and sixth year medical students and lasts one week. During the course all aspects of medical informatics are considered. Programming, databases, information systems, signal analysis, pattern recognition, expert systems, etc. are explained. Lectures alternate with hands-on experience. The subjects discussed in the lectures are rehearsed during the practical sessions, so that gaps in the student´s knowledge are immediately detected. The blockcourse has been positively rated by the students.
Keywords: Education; Medical Informatics; Computer-assisted Instruction; Medical Decision Making